Exploring fungal diversity: Passalora, Pseudocercospora, Sirosporium and Zasmidium on Brazilian plants - Silva, Meiriele da (2016)
Fungi cercosporoid are one of the largest groups of microfungi, with over than 2000 associated names, including several genera of Mycosphaerella and Mycosphaerella-like sexual morph. The cercosporoids are cosmopolitan fungi and are highly diverse especially in tropical and subtropical countries. Cercoporoid fungi vary from being saprobic, hyperparasitic and plant pathogenic, in the last case they are known to causes several important diseases in several crops. In the last years, the taxonomy of cercosporoid fungi has undergone significant changes. The application of molecular techniques have generated new informations that are helping the understanding of the phylogenetic relationships leading to a re-structuration of the classification system of this group of fungi with rearrangements, fusion of genera and recognition of new genera as distinct. In this study, a total of 27 Pseudocercospora spp., 7 Passalora spp., 4 Zasmidium spp. and one Sirosporium were collected, cultivated and subjected to a multigene analysis. Four genomic regions (LSU, ITS, tef1 and actA) were used to performed a Bayesian analysis with combined ITS, actA and tef1 sequence alignment. Our results based on DNA phylogeny integrated with morphology, revealed a rich diversity with eighteen new species to be described, namely: Pseudocercospora aeschynomenicola, Ps. diplusodonii, Ps. emmotunicola, Ps. manihotii, Ps. perae, Ps. planaltinensis, Ps. pothomorphes, Ps. sennae-multijugae, Ps. solani-pseudocapsicicola, Ps. vassobiae, Ps. wulffiae, Ps. xylopiae, Passalora dasyphyllii, Sirosporium tocoyenae, Zasmidium aspidospermae, Z. brosimii, Z. peixotoana and Z. roupalina. Eleven epitype specimens were designated, Pseudocercospora bixae, P. chamaecristae, P.exilis, P. luzardii, P. plumeriifolii, P. richardsoniicola, P. rigidae, P. struthanthi, Passalora schefflerae, Pa. rubida and Pa. vicosae, three species newly reported, Ps. euphorbiacearum, Ps. tecomicola, Ps. trinidadensis and several new host records linked to known cercosporoid in Brazil. Additionally, the phylogenetic position of Camptomeris leucaenae was investigated for the first time based in sequences of the large subunit ribosomal (LSU). This study confirmed that C. leucaenae belongs to Mycosphaerellaceae s. str. (Capnodiales, Dothideomycetes) and is closely related to Cymadothea trifolii a pathogen a native leguminous plant from Europe. The present study represents the first organized effort towards generating molecular data to support the taxonomy of cercosporoid from Brazil. It yielded information for 40 taxa, representing only a small fraction of yet unknown species diversity in the country. Many additional species still need to be collected and recollected to enable a better understanding of systematic of cercosporoid fungi in Brazil.